Synergistic multiscale structural engineering of hollow carbon spheres and 3D folded architectures for interfacial solar steam generation - Jyoti K; Dowon Moon; Jinsil Kim; Hamin Lee; Yunha Jung; Hyun Soo Han; Tatachari Santhanagopalan Shridharan; Jin-Sung Park; In Sun Cho (Chemical Engineering Journal, 2026)

Camellia sinensis (L.) mitigates copper oxide nanoparticles-induced lung inflammation and mucus production through suppressing MAPK signaling and MUC5AC - Woong-Il Kim; Seol Jang; So-Won Pak; Sin-Hyang Park; Ba-Reun Jin; Jong-Choon Kim; Changjong Moon; Joong-Sun Kim; Young-Kwon Cho; Taesoo Kim; In-Sik Shin (Molecular & Cellular Toxicology, 2026)

Synergistic mechanochemical surface reconstruction of perovskite layer for efficient and stable carbon-electrode perovskite devices - Sae Jin Sung; Yeonsu Jung; Seongsik Nam; Sehyun Kang; Jong Jin Chung; Gabkyung Seo; Jason J. Yoo; Yoo Jae Jeong; Shanshan Gao; In Sun Cho; Nam Joong Jeon; Seong Sik Shin (Chemical Engineering Journal, 2026)

Future variability in groundwater-surface water interactions: Implications for streamflow and its components using SWAT-MODFLOW 6 and CMIP 6 projections - Suh-Ho Lee; Hye-Ji Kim; In-Hee Cho; Seong-Sun Lee; Hyemin Park; Youn-Tae Kim; MoonSu Kim; Kang-Kun Lee (Journal of Hydrology, 2026)

Flame-constructed spinel Fe-Ni-O nanoparticles-on-nanosheet superstructures for scalable and durable hydrogen production - Jin Sil Kim; Sung Won Hwang; Yoo Jae Jeong; Runfa Tan; Ha Min Lee; Arumugam Sivanantham; In Sun Cho (Chemical Engineering Journal, 2026)

BiVO4–Bi–V2O3 ternary composite crafted in situ via self-decomposition synthesis for high-performance solar-driven steam generation and wastewater remediation - Tatachari Santhanagopalan Shridharan; Runfa Tan; Jyoti K; Jaeyeong Lee; Jong Seong Bae; In Sun Cho (Journal of Water Process Engineering, 2025)

Explainable AI-based evaluation of factors affecting heavy metal removal by microalgae-based adsorbents - Gyu-Ri Choi; Heejin Yang; Jong Ho Lee; Tan Runfa; In Sun Cho; Seong-Jik Park; Chang-Gu Lee; Jin-Kyu Kang (Journal of Applied Phycology, 2025)

ELF18-INDUCED LONG NONCODING RNA 25 positively regulates the pathogen defense-related CYP82C2 expression in Arabidopsis - Jun Sung Seo; Moon-Joo Lee; Jimin Lee; Nuri Oh; So-Young Jang; Ye In Cho; Jin-Ho Kang; Jang-Kyun Seo; Hye Sun Cho; Moonhyuk Kwon; Choonkyun Jung (Journal of Plant Biology, 2025)
Long noncoding RNAs (lncRNAs) are emerging as important regulators of gene expression during plant immune responses. In this study, we identified a novel lncRNA, ELF18-INDUCED LONG NONCODING RNA 25 ( ELENA25 ), located in the intergenic region between AT4G31960 and CYTOCHROME P450, family 82, subfamily C, polypeptide 2 ( CYP82C2 ) in Arabidopsis. ELENA25 was initially identified through custom lncRNA microarray data. Here, its full-length sequence (810 bp) was determined using primer walking and confirmed by sequencing. ELENA25 expression was preferentially induced by flg22, a bacterial pathogen-associated molecular pattern (PAMP), in a late-phase and FLS2 receptor-dependent manner. Neighboring genes AT4G31960 and CYP82C2 were also flg22-inducible, with expression abolished in the fls2 mutant background. To assess whether ELENA25 regulates the expression of nearby genes, we generated ELENA25 -overexpressing (OX) and knockout (KO) plants. In ELENA25 OX lines, CYP82C2 expression was significantly upregulated under normal and flg22-treated conditions, while AT4G31960 expression remained unchanged. Conversely, in the elena25 mutants (KO), CYP82C2 expression was significantly reduced, indicating that ELENA25 positively regulates CYP82C2 transcription. Expression levels of other nearby cytochrome P450 genes, including CYP82C3 and CYP82C4 , and other indole glucosinolate-related CYP genes were not affected by ELENA25 expression changes. Collectively, our results demonstrate that ELENA25 is a flg22-inducible lncRNA that specifically enhances CYP82C2 expression in a FLS2-dependent manner. This study provides new insights into the role of lncRNAs in plant innate immunity, highlighting ELENA25 as a positive regulator of defense-related gene expression.

Visible light-driven selective redirection of phenolic carbon in heterogeneous Fenton-like reaction - Youn-Jun Lee; Prakash Govindaraj; Yoo Jae Jeong; Runfa Tan; In Sun Cho; Seong-Jik Park; Hern Kim; Chang-Gu Lee; Pedro J.J. Alvarez (Water Research, 2025)

Defect-engineered black indium oxide: A high-performance photothermal material for solar-driven water purification - Runfa Tan; Tatachari Santhanagopalan Shridharan; Jong Ho Lee; Mukkath Joseph Josline; Jae Yeong Lee; Jong Seong Bae; Arumugam Sivanantham; Yoo Jae Jeong; Jae-Hyun Lee; Sangwook Lee; In Sun Cho (Desalination, 2025)

Simple synthesis of K/P co-doped graphitic carbon nitride to enhance photocatalytic performance under simulated solar irradiation - Jong-Min Lee; Youn-Jun Lee; Jong Ho Lee; Runfa Tan; Jin-Sil Kim; In Sun Cho; Seong-Jik Park; Chang-Gu Lee (Environmental Research, 2025)

UV photoreduction-driven heterogeneous fenton-like process: Long-term reactivation of fenton sludge-derived biochar and enhanced acetaminophen degradation - Heejin Yang; Sung-Hyo Jung; Jong Ho Lee; In Sun Cho; Seong-Jik Park; Chang-Gu Lee (Journal of Water Process Engineering, 2024)

Enhancing acetaminophen removal through persulfate activation with ZnCl2-SPI biochar: A study on reactive oxygen species contribution according to acetaminophen concentration - Heejin Yang; Gyu-Ri Choi; Yoo Jae Jeong; In Sun Cho; Seong-Jik Park; Chang-Gu Lee (Chemical Engineering Journal, 2024)

Unique photothermal material: Copper phosphate (Cu3P2O8) with broadband visible-to-near-infrared absorption properties for efficient solar steam generation - Tatachari Santhanagopalan Shridharan; Jong Ho Lee; Runfa Tan; Arumugam Sivanantham; Hyun Soo Han; Hyun Suk Jung; In Sun Cho (Desalination, 2024)

Solution-processed nanoporous and faceted CuO electrocatalyst for enhanced solar-to-hydrogen and nitrate-to-ammonia production - Runfa Tan; Min Je Kang; Li Qu; Sung Won Hwang; Seo Yeong Hong; Yoo Jae Jeong; Hyun Soo Han; Dong Hoe Kim; Sangwook Lee; In Sun Cho (Journal of Water Process Engineering, 2024)

Dry reforming process using microwave plasma generator with high carbon dioxide conversion efficiency for syngas production - Chang Hyun Cho; Ji Hun Kim; Jong Keun Yang; In Sun Park; Yong-Sup Choi; In Je Kang (Fuel, 2024)

Mechanochemical activation of silicon photothermal material for efficient interfacial solar desalination and wastewater purification - Tatachari Santhanagopalan Shridharan; Arumugam Sivanantham; Jong Ho Lee; Seo Yeong Hong; Yoo Jae Jeong; Seong Sik Shin; In Sun Cho (Chemical Engineering Journal, 2024)

Graphitic-carbon-nitride-hydrophilicity-dependent photocatalytic degradation of antibiotics with different log Kow - Jong-Min Lee; Youn-Jun Lee; Yoo Jae Jeong; In Sun Cho; Eun Hea Jho; Seong-Jik Park; Chang-Gu Lee (Chemosphere, 2024)

In situ electrolyte replenishment with atmospheric pressure-chemical/electrochemical vapour deposition for molten carbonate fuel cells - Kab In Kim; Jae Kwan Bae; Emilio Audasso; Albert Won Cho; Young Bae Jun; Hyun Seo Park; Seong-Cheol Jang; Yong Soo Cho; Han Sung Kim; Sun-Hee Choi; Sung Pil Yoon (Chemical Engineering Journal, 2023)

The inhibitory mechanism of humic acids on photocatalytic generation of reactive oxygen species by TiO2 depends on the crystalline phase - Youn-Jun Lee; Yoo Jae Jeong; In Sun Cho; Chang-Gu Lee; Seong-Jik Park; Pedro J.J. Alvarez (Chemical Engineering Journal, 2023)

Defect-enriched red phosphorus nanosheets as efficient and stable photothermal absorber material for interfacial solar desalination - Tatachari Santhanagopalan Shridharan; Arumugam Sivanantham; Runfa Tan; Seo Yeong Hong; Dong Hoe Kim; In Sun Cho (Desalination, 2023)

Mechanisms of interactions in pattern-recognition of common glycostructures across pectin-derived heteropolysaccharides by Toll-like receptor 4 - Gyu Hwan Hyun; In Ho Cho; Yoon Young Yang; Da-Hye Jeong; Yun Pyo Kang; You-Sun Kim; Seul Ji Lee; Sung Won Kwon (Carbohydrate Polymers, 2023)

CO2-mediated thermocatalytic monomer recovery from decomposable drinking straw waste over a tricalcium phosphate catalyst - Seonho Lee; Tak Hyun You; In Sun Cho; Jechan Lee (Chemical Engineering Journal, 2023)

Facile synthesis of N vacancy g-C3N4 using Mg-induced defect on the amine groups for enhanced photocatalytic •OH generation - Youn-Jun Lee; Yoo Jae Jeong; In Sun Cho; Seong-Jik Park; Chang-Gu Lee; Pedro J.J. Alvarez (Journal of Hazardous Materials, 2023)

Inverse opal-structured all-in-one water purification filter designed for the effective removal of multi-pollutants - Hee Jung Kim; Gill Sang Han; Jaesung Kim; Young Ju Kim; Jin Hyuk Choi; Jae Myeong Lee; Geon Woo Yoon; Hongshin Lee; In Sun Cho; Jaesang Lee; Hyun Suk Jung (Journal of Water Process Engineering, 2023)

A rice seed-specific glycine-rich protein OsDOR1 interacts with GID1 to repress GA signaling and regulates seed dormancy - Sooyeon Kim; Sun Mi Huh; Hay Ju Han; Gang Seob Lee; Yong-Sic Hwang; Mi Hyun Cho; Beom-Gi Kim; Ji Sun Song; Joo Hee Chung; Myung Hee Nam; Hyeonso Ji; Kyung-Hwan Kim; et al. (Plant Molecular Biology, 2023)

Synergistic role of hydrogen treatment and heterojunction in H-WO3-x/TiO2-x NT/Ti foil-based photoanodes for photoelectrochemical wastewater detoxification and antibacterial activity - Mahadeo A. Mahadik; In-Seon Hwang; Weon-Sik Chae; Hyun Hwi Lee; Sun Hee Choi; Min Cho; J.S. Jang (Chemosphere, 2023)

Clinical features and epidemiology of severe fever with thrombocytopenia syndrome in dogs in the Republic of Korea: an observational study (2019–2020) - Sun-Woo Han; Ye-In Oh; Ji-Min Rim; Yoon-Kyoung Cho; Dong-Hoo Kim; Jun-Gu Kang; Kyoung-Seong Choi; Joon-Seok Chae (Veterinary Research Communications, 2022)

Construction of full-length infectious cDNA clones of two Korean isolates of turnip mosaic virus breaking resistance in Brassica napus - Zheng-Xing Song; Eun-Young Seo; Wen-Xing Hu; Jong-Hyeon Jeong; Jae Sun Moon; Kang-Hee Kim; Won-Seob Eom; In-Sook Cho; John Hammond; Hyoun-Sub Lim (Archives of Virology, 2022)

A preliminary study of natural environmental change and its impact on early Late Paleolithic people in the northeast central Korean Peninsula during Marine Istope Stage 3 (40–30k cal a bp ) - Sangheon Yi; Chang‐Gyun Han; Keun‐Chang Oh; In Sun Seo; Dongwook Kim; Jaeyoung Lee; Min Han; Hanwoo Choi; Jaesoo Lim; Sujeong Park; Chang‐Pyo Jun; Taesop Cho (Journal of Quaternary Science, 2022)
We comprehensively analyzed sediments obtained from an archeological excavation. A trench sediment profile of Maedun Cave (MC), South Korea, was analyzed geoarchaeologically. Multi‐proxy analyses (palynomorphs, grain size, magnetic susceptibility, animal bones and artifacts) reflected the vegetation, hydroclimate and lives of prehistoric people at Marine Isotope Stage (MIS) 3 (ca. 40–30k cal a bp ) in the early Late Paleolithic. The palynoflora consisted of pollen and non‐pollen palynomorphs. Under the air‐circulation system in the cave, anemophilous pollen flowed in during the day, whereas waterborne pollen and spores, and freshwater algae, were transported by flooding during the summer monsoon rainy season. Mixed conifer and deciduous broad‐leaved forest with an understory of pteridophytes flourished around the north‐east central Korean Peninsula during MIS 3. Freshwater algae and grass pollen records may reflect precipitation intensity. It is assumed that they had flowed in during flooding caused by high precipitation during the enhanced East Asian summer monsoon, corresponding to Dansgaard–Oeschger (D/O) events 5 and 8 of δ 18 O GISP2 and Hulu Cave. The prehistoric people hunted herbivorous animals in the area around MC and sheltered inside it seasonally. They also used the grains of oats growing near the dwelling as a source of food.

Poor outcomes of early recurrent post-transplant bloodstream infection in living-donor liver transplant recipients - Si-Ho Kim; Seok Jun Mun; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Gyu-Seong Choi; Jong Man Kim; Jae-Won Joh; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Risk factors for development and mortality of invasive pulmonary Aspergillosis in kidney transplantation recipients - Hyeri Seok; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Woo Seong Huh; Jae Berm Park; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Comparison of the clinical characteristics and outcomes of bloodstream infections caused by Raoultella species and Klebsiella pneumoniae - Kyung-Wook Hong; Yun-Hong Cheon; Kyunglan Moon; Sun In Hong; Byung-Han Ryu; Oh-Hyun Cho; In-Gyu Bae (Infectious Diseases, 2020)

Emergence of vancomycin-resistant Enterococcus faecium ST1421 lacking the pstS gene in Korea - Hye Mee Kim; Doo Ryeon Chung; Sun Young Cho; Kyungmin Huh; Cheol-In Kang; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Clinical factors influencing the performance of bacterial multiplex polymerase chain reaction in patients with community-onset pneumonia - Ga Eun Park; Kyong Ran Peck; Jae-Hoon Ko; Cheol-In Kang; Sun Young Cho; Doo Ryeon Chung; Nam Yong Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Clinical effectiveness of oral antimicrobial therapy for acute pyelonephritis caused by extended-spectrum β-lactamase-producing Enterobacteriales - Si-Ho Kim; Kyoung Ree Lim; Hyunju Lee; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Evaluating the optimal dose of teicoplanin with therapeutic drug monitoring: not too high for adverse event, not too low for treatment efficacy - Si-Ho Kim; Cheol-In Kang; Kyungmin Huh; Sun Young Cho; Doo Ryeon Chung; Soo-Youn Lee; Yae-Jean Kim; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

First report of zucchini yellow mosaic virus in muskmelon (Cucumis melo) in Korea - In-Sook Cho; Bong-Nam Chung; Sun-Jung Kwon; Ju-Yeon Yoon; Gug-Seoun Choi; Boram Kim; John Hammond; Hyoun-Sub Lim (Journal of Plant Pathology, 2019)

Reversine induces caspase-dependent apoptosis of human osteosarcoma cells through extrinsic and intrinsic apoptotic signaling pathways - Jae-Sung Kim; In-A Cho; Kyeong-Rok Kang; HyangI Lim; Tae-Hyeon Kim; Sun-Kyoung Yu; Heung-Joong Kim; Seul Ah Lee; Sung Min Moon; Hong Sung Chun; Chun Sung Kim; Do Kyung Kim (Genes & Genomics, 2019)

Inappropriate empirical antibiotic therapy does not adversely affect the clinical outcomes of patients with acute pyelonephritis caused by extended-spectrum β-lactamase-producing Enterobacteriales - Si-Ho Kim; Suhyun Oh; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Follow-up blood cultures add little value in the management of bacteremic urinary tract infections - HyeJin Shi; Cheol-In Kang; Sun Young Cho; Kyungmin Huh; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Pathogenic significance of hemorrhagic pneumonia in hematologic malignancy patients with Stenotrophomonas maltophilia bacteremia: clinical and microbiological analysis - Si-Ho Kim; Min Kyeong Cha; Cheol-In Kang; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

TRPV4-Mediated Anti-nociceptive Effect of Suberanilohydroxamic Acid on Mechanical Pain - Geunyeol Choi; Tae-Jin Yang; Sungjae Yoo; Seung-In Choi; Ji Yeon Lim; Pyung Sun Cho; Sun Wook Hwang (Molecular Neurobiology, 2019)

Ascorbic Acid Attenuates Lead-Induced Alterations in the Synapses in the Developing Rat Cerebellum - Sung Min Nam; In-Sun Cho; Jin Seok Seo; Tae-Hun Go; Ji-Hye Kim; Sang-Soep Nahm; Byung-Joon Chang; Jong-Hwan Lee (Biological Trace Element Research, 2019)

Identification of rehmannia virus 1, a novel putative member of the genus Closterovirus, from Rehmannia glutinosa - Sun-Jung Kwon; Meilan Jin; In-Sook Cho; Ju-Yeon Yoon; Gug-Seoun Choi (Archives of Virology, 2018)

Factors affecting the public awareness and behavior on antibiotic use - Kyungmin Huh; Doo Ryeon Chung; So Hyun Kim; Sun Young Cho; Young Eun Ha; Cheol-In Kang; Kyong Ran Peck; Jae-Hoon Song (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Seismicity of the 2016 ML 5.8 Gyeongju earthquake and aftershocks in South Korea - Jimin Lee; Yonggyu Ryoo; Sun Cheon Park; Young Mo Ham; Jong Soo Park; Myeong Su Kim; Sang Mi Park; Hyen Geom Cho; Keun Su Lee; In Sun Kim; Hye Su Kim; Sunhee Bae (Geosciences Journal, 2018)

Real Data Assimilation Using the Local Ensemble Transform Kalman Filter (LETKF) System for a Global Non-hydrostatic NWP model on the Cubed-sphere - Seoleun Shin; Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Kwangjae Sung; Kyoungmi Cho; Youngsoon Jo; Jung-Eun Kim; In-Hyuk Kwon; Sujeong Lim; Ji-Sun Kang (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Complete nucleotide sequence of a highly divergent cherry-associated luteovirus (ChALV) isolate from peach in South Korea - Davaajargal Igori; Seungmo Lim; Dasom Baek; In Sook Cho; Jae Sun Moon (Archives of Virology, 2017)

First report of cherry virus A infecting Prunus mume in South Korea - Seungmo Lim; Davaajargal Igori; Dasom Baek; In-Sook Cho; Gug-Seoun Choi; Jae Sun Moon (VirusDisease, 2017)

Complete nucleotide sequence and genome organization of peach virus D, a putative new member of the genus Marafivirus - Davaajargal Igori; Seungmo Lim; Dasom Baek; San Yeong Kim; Euncheol Seo; In-Sook Cho; Gug-Seoun Choi; Hyoun-Sub Lim; Jae Sun Moon (Archives of Virology, 2017)

Molecular detection and characterization of a divergent isolate of Plantago asiatica mosaic virus in Plantago asiatica - Seungmo Lim; Davaajargal Igori; Fumei Zhao; Yun Su Do; In-Sook Cho; Gug-Seoun Choi; Jae Sun Moon (VirusDisease, 2016)

LC-ESI-MS/MS analysis of phosphodiesterase-5 inhibitors and their analogues in foods and dietary supplements in Korea - Ji Hye Jeong; Ji Hyun Lee; Hyung Joo Kim; Hyoung Joon Park; In Sun Hwang; Kyoung Moon Han; Chang-Yong Yoon; Sooyeul Cho; Woo Seong Kim (Food Additives & Contaminants Part B-Surveillance, 2016)

Genomic detection and characterization of a Korean isolate of Little cherry virus 1 sampled from a peach tree - Seungmo Lim; Davaajargal Igori; Ran Hee Yoo; Fumei Zhao; In-Sook Cho; Gug-Seoun Choi; Hyoun-Sub Lim; Su-Heon Lee; Jae Sun Moon (Virus Genes, 2015)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

A novel gibberellin 2-oxidase gene CaGA2ox1 in pepper is specifically induced by incompatible plant pathogens - Yeon Lee; Young-Cheol Kim; Soo Yong Kim; In-Jung Lee; Doil Choi; Kyung-Hee Paek; Hye Sun Cho; Suk Yoon Kweon; Jeong Mee Park (Plant Biotechnology Reports, 2012)

Simple freezing and thawing protocol for long-term storage of harvested fresh Undaria pinnatifida - Jae-Suk Choi; Bo-Bae Lee; Sun Ju An; Jae Hak Sohn; Kwang Keun Cho; In Soon Choi (Fisheries Science, 2012)

Isolation of the groESL cluster from Vibrio anguillarum and PCR detection targeting groEL gene - Dong-Gyun Kim; Yu-Ri Kim; Eun-Young Kim; Hyun Min Cho; Sun-Hee Ahn; In-Soo Kong (Fisheries Science, 2010)

A novel mutation in Hr causes abnormal hair follicle morphogenesis in hairpoor mouse, an animal model for Marie Unna Hereditary Hypotrichosis - In Cheol Baek; Jeong Ki Kim; Kyu-Hyuk Cho; Dal-Sun Cha; Jae-Woo Cho; Jong Keun Park; Chang-Woo Song; Sungjoo Kim Yoon (Mammalian Genome, 2009)

Prevalence and molecular characterization of meq in feather follicular epithelial cells of Korean broiler chickens - Jung-Won Kang; Sun-Hee Cho; In-Pil Mo; Dong-Woo Lee; Hyuk-Joon Kwon (Virus Genes, 2007)

A rice dehydration-inducible SNF1-related protein kinase 2 phosphorylates an abscisic acid responsive element-binding factor and associates with ABA signaling - Min-Ju Chae; Jung-Sook Lee; Myung-Hee Nam; Kun Cho; Ji-Yeon Hong; Sang-A Yi; Seok-Cheol Suh; In-Sun Yoon (Plant Molecular Biology, 2006)

Characterization of copper, zinc superoxide dismutase from a cartilaginous shark species, Scyliorhinus torazame (Carcharhiniformes) - Yoon Kwon Nam; Young Sun Cho; Keun-Yong Kim; In Chul Bang; Ki Hong Kim; Sung Koo Kim; Dong Soo Kim (Fish Physiology and Biochemistry, 2006)

Identification of differentially expressed genes involved in spine formation on seeds ofDaucus carota L. (carrot), using annealing control primer (ACP) system - Jong-Sug Park; In Sun Kim; Moon Soo Cho; Shin Park; Sang Gyu Park (Journal of Plant Biology, 2006)

Decolorization of triphenylmethane and azo dyes by Citrobacter sp. - Sun-Young An; Sang-Ki Min; In-Ho Cha; Yong-Lark Choi; Young-Su Cho; Cherol-Ho Kim; Young-Choon Lee (Biotechnology Letters, 2002)

A new class II rice chitinase, Rcht2, whose induction by fungal elicitor is abolished by protein phosphatase 1 and 2A inhibitor - Cha Young Kim; Sang Wan Gal; Mi Sook Choe; Sun Yong Jeong; Soo In Lee; Yong Hwa Cheong; Sang Hyoung Lee; Young Ju Choi; Chang-deok Han; Kyu Young Kang; Moo Je Cho (Plant Molecular Biology, 1998)